2007
DOI: 10.1096/fasebj.21.5.a680
|View full text |Cite
|
Sign up to set email alerts
|

Geophagia is not associated with parasite transmission in Zanzibar, Tanzania

Abstract: The healthfulness of geophagia, the purposive consumption of earth, is contested. One way in which geophagia may be harmful is as a vector for the transmission of geohelminths. In this study, we pose two questions in a representative sample of 970 pregnant women from Pemba Island, Zanzibar, Tanzania: Is consumed earth a vector for geohelminth infection? Do geophagists have differential parasitic infection? Parasitological analyses were conducted on 42 samples of Pemban soil. Cross‐sectional data about pica b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On the other hand, geophagia has been associated with lead poisoning, hyperkalemia, phosphorous intoxication, dental injury and other undesirable effects including low bone mineralization [7,16]. Several studies have reported associations between geophagia and anaemia, and between geophagia and deficient ferritin levels [1,[17][18][19]. Zinc deficiency has been observed to promote pica in young children [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, geophagia has been associated with lead poisoning, hyperkalemia, phosphorous intoxication, dental injury and other undesirable effects including low bone mineralization [7,16]. Several studies have reported associations between geophagia and anaemia, and between geophagia and deficient ferritin levels [1,[17][18][19]. Zinc deficiency has been observed to promote pica in young children [20].…”
Section: Introductionmentioning
confidence: 99%
“…Despite conflicting views, several evidence point to some nutritional benefits of geophagia. Whereas other researchers have speculated that geophagia during pregnancy may induce iron deficiency anaemia, others have indicated that geophagia may, in fact, be an adaptation to iron deficiency [1,3,18,21]. The high prevalence of geophagia among anaemic pregnant women sparks a quest for knowledge of the potentially available mineral contents of the lithospheric substances ingested.…”
Section: Introductionmentioning
confidence: 99%